Study of roundwood sorting on the simulation model of longitudinal chain conveyor - Sarbassova, Nurbanu; Umurzakova, Anara; Kladiev, Sergey (Institute of Advanced Engineering and Science, 2024)
When sorting roundwood on chain longitudinal conveyors of considerable length, there is an error in moving the selected roundwood assortment to the place of discharge into the accumulator, which increases in proportion to the length of the sorting line. Currently, conveyors of limited length are used. The accumulators are located on both sides of the conveyor. This reduces the transportation error. Sometimes the sorting yard does not allow placing a short conveyor on it or there is a considerable amount of assortments. In this case, it is necessary to use a conveyor of considerable length. The paper proposes a new method of sorting roundwood on longitudinal chain conveyors of considerable length. This reduces the tracking error of the assortment movement. Angular displacement sensors of the leading and driven sprockets of the closed plate chain of the sorting conveyor are used as sensors of angular displacements. The shafts of both sensors are mechanically connected to the shafts of the driving and driven sprockets, respectively. The results of simulation modeling of the sorting control system with complex mechanical system confirmed the possibility of practical application of the proposed method to reduce the tracking error of the sorted cargo. The results of the study confirm the possibility of practical application of the device for operation on longitudinal conveyors.